Stock and sovereign returns linkages: time-varying causality and extreme-quantile determinants - Afonso, António (2025)
We employ a cross-quantilogram approach to assess relationships between quantiles of stock returns and sovereign yields, in the U.S. and Germany, in the period 1990-2024. Specifically, we focus on the lowest 5% quantile of stock returns and the highest 5% quantile of bond returns, providing insights into tail dependencies, crucial during market downturns and periods of heightened volatility. We also measure causality in volatilities extending well-known approaches analyzing volatility transmission. We find significant cross-market relationships between U.S. and German stock and bond markets, influenced by economic crises, macroeconomic dynamics, and monetary policy interventions, and financial stress play a crucial role.